Filsafat Progresivisme Dalam Kurikulum Merdeka - Khairani, Neneng (Yayasan Sembilan Pemuda Indonesia, 2023)
John Dewey created a philosophical approach to education known as progressivism. Progressivism is an educational philosophy that wants student freedom and independence in the learning process. This philosophical also emphasizes a process of change which is marked by progress of teacher and student creativity. In Indonesia today, the application of the concept of independent learning has led to the development of students according to their interests and talents through differentiated learning, which of course is in accordance with the philosophy of progressivism. Progressivism requires student-centered learning to support progress, providing opportunities for students to become skilled and have the knowledge needed to be equipped to face educational progress according to the times.